What We're Missing: A Descriptive Analysis of Part-Day Absenteeism in Secondary School. (April 2017) - Whitney, Camille R.; Liu, Jing
For schools and teachers to help students develop knowledge and skills, students need to show up to class. Yet absenteeism is prevalent, especially in secondary schools. This study uses a rich data set tracking class attendance by day for over 50, 000 middle and high school students from an urban district in academic years 2007–2008 through 2012–2013. Our results extend and modify the extant findings on absenteeism that have been based almost exclusively on full-day absenteeism, missing class-by-class absences. Notably, part-day absenteeism is responsible for as many classes missed as full-day absenteeism, raising chronic absenteeism from 9% to 24% of secondary-grades students. Incorporating part-day absences sharply increases the chronic absenteeism gap between underrepresented minority students and their peers. Both full- and part-day absenteeism show a discrete jump at the point of transition from middle school to high school, but full-day absenteeism then declines whereas part-day absenteeism remains high in Grades 10 and 11 and increases again in Grade 12. Whereas 55% of full-day absences are unexcused, 92% of part-day absences are unexcused. Absenteeism from individual classes varies considerably by time of day but less by class subject matter.